FAKTOR-FAKTOR YANG MEMENGARUHI CALVING INTERVAL SAPI PERAH PADA PETERNAKAN RAKYAT DI BEBERAPA KABUPATEN/KOTA PROVINSI LAMPUNG - Al-amin, Ahmad Fauzy; Hartono, Madi; Suharyati, Sri (Jurnal Riset dan Inovasi Peternakan, 2017)
The purpose of this research were : 1) value calving intervalof dairy cattles on people’s livestocksome districts/cities at Lampung Province; 2) the factors and value factors which disturbing calving interval of dairy cattles on people livestock at some districts/cities at Lampung Province. This research was held on June-July 2016 with 37 dairy cattles, 11 farmers, and 3 inseminators at Tanggamus District, West Lampung District, and Metro City. This research used survey method. Data was analyse by multiple regression analysis.  The result showed that calving interval of dairy cattles on people’s livestock at Lampung Provinceis 15,95 month. Factors that affecting calving interval of dairy cattles on people livestock at some disricts/cities at Lampung Province were long empty period, long dry period, and long lactation. Keywords : Calving Interval, Factor, Dairy Cattle, People Livestock